2012
DOI: 10.1021/la302758g
|View full text |Cite
|
Sign up to set email alerts
|

Effective Reduction of Nonspecific Binding by Surface Engineering of Quantum Dots with Bovine Serum Albumin for Cell-Targeted Imaging

Abstract: Quantum dots (QDs) have been widely used as fluorescent probes in cell-targeted imaging. However, nonspecific binding to cellular membranes has been a major challenge. In this study, a new approach is developed for effective reduction of nonspecific binding by bovine serum albumin (BSA)-coated QDs in cell targeting. The experimental results show efficient transfer of hydrophobic QDs from organic to aqueous phase in the presence of BSA aqueous solution under ultrasonication. This ultrasonication-based approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 54 publications
2
77
0
Order By: Relevance
“…[33][34][35] Based on the unique structure of BSA, it was found that the QDs were effectively surface functionalized under ultrasonication. 21 However, SPIONs were found to cluster at an average size of 100 nm. 22 In this study, a transition process by NOBF 4 was introduced to the surface functionalization of SPIONs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[33][34][35] Based on the unique structure of BSA, it was found that the QDs were effectively surface functionalized under ultrasonication. 21 However, SPIONs were found to cluster at an average size of 100 nm. 22 In this study, a transition process by NOBF 4 was introduced to the surface functionalization of SPIONs.…”
Section: Resultsmentioning
confidence: 99%
“…29 However, in the course of dialysis against water, the inhibition of DMF decreases along with DMF being diluted gradually in the samples. Therefore, hydrophilic BSA can be anchored onto the surfaces of SPIONs by means of its chemical groups with appreciable metal affinity, 21 resulting in enhanced solubility of BSA⋅SPIONs in water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations